Gastric leaks after sleeve gastrectomy: a multicenter experience with 2,834 patients - Sakran, Nasser; Goitein, David; Raziel, Asnat; Keidar, Andrei; Beglaibter, Nahum; Grinbaum, Ronit; Matter, Ibrahim; Alfici, Ricardo; Mahajna, Ahmad; Waksman, Igor; Shimonov, Mordechai; Assalia, Ahmad (Surgical endoscopy, 2013)
Background Laparoscopic sleeve gastrectomy (LSG) remains under scrutiny as a stand-alone bariatric procedure. The most feared complication after LSG is staple line leak. Methods Eight bariatric centers in Israel participated in this study. A retrospective analysis was performed by querying all the LSG cases performed between June 2006 and June 2010. The data collected included patient demographics, anthropometrics, and operative and perioperative parameters. Results Among the 2,834 patients who underwent LSG, 44 (1.5 %) with gastric leaks were identified. Of these 44 patients, 30 (68 %) were women. The patients had a mean age of 41.5 years and a body mass index (BMI) of 45.4 kg/m 2 . Intraoperative leak tests and routine postoperative swallow studies were performed with 33 patients, and all but one patient (3 %) failed to detect the leaks. Leaks were diagnosed at a median of 7 days postoperatively: early (0–2 days) in nine cases (20 %), intermediately (3–14 days) in 32 cases (73 %), and late (>14 days) in three cases (7 %). For 38 patients (86 %), there was clinical suspicion, later confirmed by imaging or operative findings. Computed tomography, swallow studies, and methylene blue tests were performed for 37, 21, and 15 patients, respectively, and the results were positive, respectively, for 31 (84 %), 11 (50 %), and 9 (60 %) of these patients. Reoperation was performed for 27 of the patients (61 %). Other treatment methods included percutaneous drainage ( n = 28, 63.6 %), endoscopic placement of stents ( n = 11, 25 %), clips ( n = 1, 2.3 %), and fibrin glue ( n = 1, 2.3 %). In 33 of the patients (75 %), the leak site was found in the upper sleeve near the gastroesophageal junction. The median time to leak closure was 40 days (range, 2–270 days), and the overall leak-related mortality rate was 0.14 % (4/2,834). Conclusion Gastric leak is the most common cause of major morbidity and mortality after LSG. Routine tests to rule out leaks seem to be superfluous. Rather, selective utilization is recommended. Management options vary, depending mainly on patient disposition. An accepted algorithm for the diagnosis and treatment of gastric leak has yet to be proposed.